Pengaruh Budaya Organisasi, Motivasi, Dan Disiplin Kerja, Terhadap Kepuasan Kerja Karyawan Di Ma’had Abu Ubaidah Bin Al Jarrah Medan - M Y Hanafia (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This research was conducted to examine how much influence organizational culture, motivation, and work discipline have on job satisfaction of employees of Ma'had Abu Ubaidah Bin Al Jarrah Medan. This study uses descriptive quantitative methods using a normative approach (legal research) for secondary data and an empirical approach (juridical sociological), to obtain primary data through field research (field research). The total population is 85 people with a sample size of a population. Data processing techniques used SPSS 20. The results showed that the influence of organizational culture, motivation, and work discipline on job satisfaction of employees of Ma'had Abu Ubaidah Bin Al Jarrah Medan, based on the following indicators: First, there is an influence between organizational culture and satisfaction. work which means a good organizational culture affects employee job satisfaction. Second, there is an influence between motivation on job satisfaction, which means that employees who are motivated to work affect job satisfaction.